Gestão de resíduos grupo D: recuperação de plásticos recicláveis em um hospital público da cidade de São Paulo - Fernandes, Renata Oliveira (2019)
Health Care Waste (SSR) is waste generated by providers of medical, dental, laboratory, pharmaceutical and educational and research institutions related to human and animal care. Part of this waste generated is classified as common, recyclable or not. The adoption of prior separation and disinfection mechanisms allows the recycling of paper, metals, aluminum, plastics and glass. Considering the possibility of establishing a plastic waste recovery program, the question that guides this research is: How is the management of plastic waste recyclable in a hospital environment? It has as general objective to evaluate the routine and internal management of plastic generated in the hospital in the sectors: care (Maternity), administrative (Warehouse) and nutrition and dietetics (SND). For this, this study used a qualitative approach, through a case study, of a descriptive nature. The data collection was divided in two steps in the first one was used of checklist to survey the nonconformities. In the second stage the data were collected through a questionnaire, in order to measure the respondents' knowledge about the RSS, besides the behavior in the treatment of RSS. In analyzing the occurrence of nonconformities, the presence of recyclable plastic waste in containers for Group D waste destined for organic waste was verified, in addition to the mixture with infectious residues. In the next stage, the questionnaire was applied to 62 professionals, who had the following predominant female profile, most with ages between 31 and 40 years, 30.65% with higher level, 87.10% have between 1 and 20 years of professional experience. Regarding the knowledge of the RSS, classification and management stages 91.94% stated they have knowledge of what they are RSS, with regard to RSS ranking 48.39% know. When asked about the steps of waste management 54.84% of the sample is unaware of the steps. Regarding the disposal of plastic waste 58.06% answered that they discard in the container for common waste. Regarding the environmental behavior related to the disposal of plastic waste, most of the respondents stated that they discarded the residue in the nearest container. This study concluded that although the hospital did not contemplate plastic waste in its Management Plan, the adoption of actions aimed at recovery and referral of waste as paper / cardboard for recycling became notorious in the institution, where it was observed the need for inclusion of plastic waste. However, sensitizing the collaborators in relation to the initiative is a crucial factor to obtain positive results, considering that these are the main agents of RSS management. Therefore, it is necessary to increase investments by the managers of the establishments in permanent continuing education programs, so that employees can understand the importance of proper management of RSS and recycling to the hospital and especially to the environment. It should be noted that this work identifies actions and seeks concepts to support waste management models that can be recycled, focusing on plastic waste, as well as contributing to the construction of RSS knowledge using PDCA quality tools and Ishikawa Diagram, contributing with the foundation theory of such subjects. To this end, the contribution to practice presented a plan of action with strategies developed regarding the management of plastic waste, presenting the solutions to be adopted in the short, medium and long term.